2022
DOI: 10.3390/agronomy12092111
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Soil Organic Matter Content Based on Feature Band Selection with ZY1-02D Hyperspectral Satellite Data in the Agricultural Region

Abstract: Soil organic matter (SOM) is an essential nutrient for crop growth and development. Hyperspectral satellite images with comprehensive spectral band coverage and high spectral resolution can be used to estimate and draw a spatial distribution map of SOM content in the region, which can provide a scientific management basis for precision agriculture. This study takes Xinzheng City, Henan Province’s agricultural area, as the research object. Based on ZY1-02D hyperspectral satellite image data, the first derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…However, the evaluation of model performance, as measured using R 2 and RMSE, varies significantly across different studies because of variations in sample collection methods, spectral processing techniques, and model construction approaches. These variations can significantly impact the accuracy and reliability of spectral modeling [52,53]. The PLSR model can identify system information and noise and permits regression modeling provided that the number of sample points is less than the number of variables.…”
Section: Feasibility Of Inverse Som Using Hyperspectral Datamentioning
confidence: 99%
“…However, the evaluation of model performance, as measured using R 2 and RMSE, varies significantly across different studies because of variations in sample collection methods, spectral processing techniques, and model construction approaches. These variations can significantly impact the accuracy and reliability of spectral modeling [52,53]. The PLSR model can identify system information and noise and permits regression modeling provided that the number of sample points is less than the number of variables.…”
Section: Feasibility Of Inverse Som Using Hyperspectral Datamentioning
confidence: 99%
“…Especially for spectral estimation of soil salt, changes in water content will affect the content and movement of soil salt, which will have a greater impact on the spectrum [35]. Therefore, it is necessary to research the spectral impact of soil moisture and its removal methods [36]. In addition, if the estimation model based on the outdoor air-dried soil spectrum is extended to the outdoor wet soil spectrum [37], the impact of soil moisture on the spectrum must also be eliminated [38].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Studies have shown that the d-factor can be used to evaluate the uncertainty of an estimation model [19,48]. The degree of uncertainty of an estimation model is proportional to the calculated value of the d-factor; that is, the degree of uncertainty of the estimated model will increase with the increase in the calculated value of the d-factor, and the d-factor calculation formula is as follows:…”
Section: Construction and Evaluation Of The Tn Content Estimation Modelmentioning
confidence: 99%